The Editor in the Computer Age: The Wyoming View - Norman E. Roberts (Journal of Applied Communications, 1974)
There may exist in this world agricultural communicators who are not limited in their operations budget - but I doubt it. There also may be those communicators whose publication operations are the showcase of efficiency - I doubt that too.